Solar cell, stacked cell, photovoltaic module
Patent Information
- Application Number
- CN202611148985.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
AI Technical Summary
本发明在栅线中加入添加剂,该添加剂中含有镧的化合物和其他稀土化合物组成的稀土协同体系,可以捕获钠离子又能与EVA水解产生的醋酸根形成稳定的络合物,同时该添加剂中还含有能够在栅线表面形成钝化层的惰性金属,有效阻隔离子迁移和电化学腐蚀,添加剂中的稀土协同体系和惰性金属物质复配,协同提升抗PID效果。
Smart Images

Figure CN122995336A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more particularly to solar cells, tandem cells, and photovoltaic modules. Background Technology
[0002] Currently, in practical applications of photovoltaic modules, potential-induced degradation (PID) is one of the important reasons for the decline in module power. Especially in high temperature and high humidity environments, sodium ions in the module glass can easily migrate through the encapsulation film to the surface of the solar cells under the influence of a strong electric field, leading to an increase in leakage current on the surface of the solar cells, and thus causing a significant decrease in the conversion efficiency of the photovoltaic module. Summary of the Invention
[0003] This application provides a solar cell, a tandem cell, and a photovoltaic module that at least improves the anti-PID effect of the grid lines.
[0004] The first aspect of this application provides a solar cell, including: a solar cell body; A grid line, wherein the grid line is formed by curing a conductive material, the conductive material including additives, the additives comprising rare earth compounds and inert metals; Wherein, the rare earth compound is a mixture of lanthanum compounds and heavy rare earth compounds, or, The rare earth compounds are non-lanthanum light rare earth compounds, lanthanum compounds, and mixtures of heavy rare earth compounds.
[0005] Optionally, the inert metal is selected from at least one of platinum, palladium, gold and silver, and the additive also includes titanium-containing materials.
[0006] Further optionally, the inert metal includes platinum powder, the titanium-containing material includes titanium powder, the titanium powder has an average particle size of 20nm~50nm, and the platinum powder has an average particle size of 10nm~30nm.
[0007] Optionally, the lanthanum compound is lanthanum oxide and / or a lanthanum halide, the non-lanthanum light rare earth compound is selected from at least one of cerium compounds, praseodymium compounds and neodymium compounds, and the heavy rare earth compound is selected from at least one of yttrium compounds, gadolinium compounds and scandium compounds.
[0008] Alternatively, the rare earth compound may be a mixture of non-lanthanum light rare earth compounds, lanthanum compounds, and heavy rare earth compounds, wherein the non-lanthanum light rare earth compound is cerium oxide, the heavy rare earth compound is yttrium oxide, the lanthanum compound is lanthanum fluoride, and the mass ratio of cerium oxide to yttrium oxide is 1:(2~4).
[0009] Further optionally, the content of the additive is 0.175% to 1.05% based on the total mass of the conductive material as 100%.
[0010] Optionally, the additives include lanthanum fluoride, cerium oxide, yttrium oxide, titanium powder, and platinum powder, wherein the content of yttrium oxide is 0.1% to 0.5%, the content of cerium oxide is 0.05% to 0.3%, the content of titanium powder is 0.01% to 0.1%, the content of platinum powder is 0.005% to 0.05%, and the content of lanthanum fluoride is 0.01% to 0.1%.
[0011] Optionally, the conductive material further includes a conductive phase, glass powder, and an organic carrier. Based on the total mass of the conductive material (100%), the content of the conductive phase is 85% to 92%, the content of the glass powder is 2% to 5%, and the content of the organic carrier is 4% to 8%.
[0012] Alternatively, the conductive phase may include spherical silver powder and flake silver powder, wherein the average particle size of the spherical silver powder is 0.5 μm to 3 μm and the average length of the flake silver powder is 1 μm to 5 μm.
[0013] Alternatively, the mass ratio of the spherical silver powder to the flake silver powder is (1~3):1.
[0014] Alternatively, the glass powder may include lead and boron silicate glass powder, wherein the raw materials of the silicate glass powder include lead oxide, silicon oxide and boron oxide, and the mass ratio of lead oxide, silicon oxide and boron oxide is (5~7):(2~4):1.
[0015] Alternatively, the organic carrier may include ethyl cellulose and terpineol, wherein the mass ratio of ethyl cellulose to terpineol is 1:(8~10).
[0016] Alternatively, the degree of polymerization of the ethyl cellulose is 500 to 1000.
[0017] A second aspect of this application provides a stacked battery, comprising: A crystalline silicon bottom cell, wherein the crystalline silicon bottom cell is the solar cell described above; A perovskite solar cell, wherein the perovskite solar cell is located on one side of the crystalline silicon substrate solar cell.
[0018] A third aspect of this application provides a photovoltaic module, including a battery string, the battery string including a plurality of solar cells as described above arranged along a first direction, and the plurality of battery strings also arranged along a second direction; A solder strip extending along a first direction and arranged along a second direction, the solder strip being used to connect two adjacent solar cells or two stacked cells along the first direction; A backplate, located on the side of the solder strip away from the back of the battery string.
[0019] The technical solution provided in this application has at least the following advantages: This invention incorporates an additive into the gate line, which contains a rare earth synergistic system composed of lanthanum compounds and other rare earth compounds. This system can capture sodium ions and form a stable complex with acetate ions generated by EVA hydrolysis. The additive also contains an inert metal that can form a passivation layer on the gate line surface, effectively preventing ion migration and electrochemical corrosion. The rare earth synergistic system and the inert metal in the additive work together to synergistically improve the anti-PID effect. Attached Figure Description
[0020] One or more embodiments are illustrated by way of example with reference to the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the drawings in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a flowchart of the method for preparing a solar cell according to an embodiment of this application; Figure 2 This is a schematic diagram of the structure of the photovoltaic module in the embodiments of this application.
[0022] Figure Labels 100. Battery string; 101. Solar cell; 120. Backsheet; 4. Solder strip. Detailed Implementation
[0023] In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0024] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0025] In the description of the embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and other components may be further included.
[0026] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "component" is also intended to include the plural form unless the context clearly indicates otherwise.
[0027] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.
[0028] In a first aspect, this application provides a solar cell, comprising: Solar cell body; A grid line, wherein the grid line is formed by curing a conductive material, the conductive material including additives, the additives comprising rare earth compounds and inert metals; Wherein, the rare earth compound is a mixture of lanthanum compounds and heavy rare earth compounds, or, The rare earth compounds are non-lanthanum light rare earth compounds, lanthanum compounds, and mixtures of heavy rare earth compounds.
[0029] By combining the above-mentioned specific rare earth compounds with the synergistic effect of inert metals, the anti-PID performance and long-term stability of solar cells can be improved from the aspects of ion capture and passivation protection. The synergistic complexation effect of specific rare earth compounds can efficiently capture the sodium ions, acetate ions and other migratory ions released by the hydrolysis of EVA film during the photovoltaic module encapsulation process, reduce the enrichment and migration of ions on the cell surface, and avoid the corrosion of the passivation layer and electrodes by ions.
[0030] In some embodiments, the inert metal is selected from at least one of platinum, palladium, gold, and silver, and the additive further includes titanium-containing materials.
[0031] In some embodiments, the inert metal includes platinum powder, and the titanium-containing material includes titanium powder. The average particle size of the titanium powder is 20 nm to 50 nm, and the average particle size of the platinum powder is 10 nm to 30 nm. Controlling the particle size of the titanium and platinum powder within the above-mentioned nanoscale range ensures good dispersion of nanoparticles in the conductive paste, avoiding internal defects in the gate lines caused by particle agglomeration. Furthermore, nanoscale titanium and platinum have higher specific surface energy and reactivity, making it easier to react and form a continuous and dense Ti-Pt-O passivation layer during sintering and solidification, thus improving ion barrier effect and interface passivation capability. If the titanium powder particle size is less than 20 nm and the platinum powder particle size is less than 10 nm, the excessively high particle surface energy easily leads to agglomeration, resulting in uneven component dispersion and failure to form a uniform and continuous passivation layer. If the titanium powder particle size is greater than 50 nm and the platinum powder particle size is greater than 30 nm, the particle reactivity is insufficient, the density of the passivation layer decreases, and the contact resistance of the gate lines increases, reducing conductivity.
[0032] In some embodiments, the lanthanum compound is lanthanum oxide and / or a lanthanum halide, the non-lanthanum light rare earth compound is selected from at least one of cerium compounds, praseodymium compounds, and neodymium compounds, and the heavy rare earth compound is selected from at least one of yttrium compounds, gadolinium compounds, and scandium compounds.
[0033] In some embodiments, the rare earth compound is a mixture of non-lanthanum light rare earth compounds, lanthanum compounds, and heavy rare earth compounds, wherein the non-lanthanum light rare earth compound is cerium oxide, the heavy rare earth compound is yttrium oxide, the lanthanum compound is lanthanum fluoride, and the mass ratio of cerium oxide to yttrium oxide is 1:(2~4), specifically, for example, 1:2, 1:3, or 1:4.
[0034] Yttrium oxide and cerium oxide are used in combination in a ratio of (2~4):1, and in conjunction with lanthanum fluoride, the ability to capture sodium ions is further enhanced, and a more stable complex is formed with acetate ions generated by EVA hydrolysis. During the sintering process, inert metal platinum and titanium-containing materials can form a continuous and dense Ti-Pt-O passivation layer at the interface between the gate line and the silicon substrate, which effectively blocks the electrochemical corrosion path and ion migration channel, while reducing the contact resistance between the gate line and the silicon substrate, and improving the conductivity and bonding force of the gate line.
[0035] In some embodiments, the content of the additive is 0.175% to 1.05% based on the total mass of the conductive material as 100%.
[0036] In some embodiments, the additives include lanthanum fluoride, cerium oxide, yttrium oxide, titanium powder, and platinum powder. The content of yttrium oxide is 0.1% to 0.5%, for example, 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%; the content of cerium oxide is 0.05% to 0.3%, for example, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, or 0.30%; and the content of titanium powder is 0.01% to 0.1%, for example, 0.01%, 0.02%, 0.03%, or 0.05%. The content of platinum powder is 0.005% to 0.05%, for example, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, or 0.05%; the content of lanthanum fluoride is 0.01% to 0.1%, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%.
[0037] In some embodiments, the conductive material further includes a conductive phase, glass powder, and an organic carrier. Based on the total mass of the conductive material (100%), the content of the conductive phase is 85% to 92%, the content of the glass powder is 2% to 5%, and the content of the organic carrier is 4% to 8%.
[0038] In some embodiments, the conductive phase comprises spherical silver powder and flake silver powder, wherein the average particle size of the spherical silver powder is 0.5 μm to 3 μm, and the average length of the flake silver powder is 1 μm to 5 μm. In some embodiments, the mass ratio of the spherical silver powder to the flake silver powder is (1 to 3):1, for example, the mass ratio of the spherical silver powder to the flake silver powder can be 1:1, 2:1, or 3:1. By blending spherical and flake silver powders within a specific particle size range in the aforementioned mass ratio, both the printability of the conductive paste and the conductivity of the grid lines can be balanced. Spherical silver powder possesses excellent sphericity and packing flowability, improving the printability of the paste, ensuring the aspect ratio and formability of fine grid printing, and reducing defects such as broken grids and incomplete printing. Simultaneously, the densest packing effect of spherical particles reduces the porosity of the grid lines, increasing their density. Flake silver powder has a larger specific surface area and layer overlap effect, forming a continuous three-dimensional conductive network within the grid lines, reducing their bulk resistance. If the proportion of spherical silver powder is too high and the proportion of flake silver powder is insufficient, the conductive network overlap will be inadequate, increasing the grid line bulk resistance. Conversely, if the proportion of flake silver powder is too high, it will reduce the paste's flowability and printability, leading to grid line sagging, increased linewidth, reduced light-receiving area of the battery, and decreased adhesion between the grid lines and the silicon substrate. Specific particle size ranges of silver powder can achieve a reasonable particle size distribution, further improving the density and conductivity uniformity of the grid lines.
[0039] In some embodiments, the softening temperature of the glass powder is 400℃~500℃, for example, 400℃, 450℃ or 500℃. In some embodiments, the glass powder includes lead and boron silicate glass powder, wherein the raw materials of the silicate glass powder include lead oxide, silicon oxide and boron oxide, and the mass ratio of lead oxide, silicon oxide and boron oxide is (5~7):(2~4):1, which can be 5:2:1, 6:1:1 or 7:4:1. The lead-borosilicate glass powder with the specific composition and proportions described above has suitable softening temperature and wettability, which can match the sintering process window of TOPCon cells: lead oxide can effectively reduce the softening temperature of the glass, improve the wettability of the glass powder on the silver powder and the antireflective film on the silicon substrate, moderately corrode the antireflective film during sintering, promote the precipitation of silver particles on the silicon surface and the formation of ohmic contacts, and reduce contact resistance; boron oxide, as a glass agglomerate, can adjust the thermal expansion coefficient and chemical stability of the glass, improve the glass's resistance to ion corrosion, and improve the glass's rheological properties; silicon oxide, as a glass network skeleton, can improve the mechanical strength and chemical stability of the glass, and prevent the precipitation of migratable ions during long-term use, which would lead to battery performance degradation; the glass powder compounded in the above proportions has suitable fluidity during sintering, which can fully corrode the antireflective film to form good ohmic contacts without over-corroding the silicon substrate and causing an increase in leakage current, while also improving the bonding strength between the grid lines and the silicon wafer.
[0040] In some embodiments, the preparation method of the lead and boron-containing silicate glass powder includes: mixing the lead oxide, silicon oxide and boron oxide in proportion, melting at 900℃~1100℃ for 1h~3h, then quenching and ball milling to a D50 of 1μm~3μm.
[0041] In some embodiments, the organic carrier comprises ethyl cellulose and terpineol, wherein the mass ratio of ethyl cellulose to terpineol is 1:(8~10), for example, it can be 1:8, 1:9 or 1:10. Combining ethyl cellulose and terpineol in the above ratio imparts suitable viscosity, rheological properties, and volatility gradient to the organic carrier, ensuring good printability of the conductive paste. Ethyl cellulose, as an organic binder, provides suitable viscosity and thixotropy to ensure that the fine grid maintains a good aspect ratio after printing, preventing sagging and collapse, while also improving the adhesion between the grid lines and the silicon wafer before sintering. Terpineol, as an organic solvent, can fully dissolve ethyl cellulose, regulate the evaporation rate of the paste, and allow the solvent to gradually evaporate during printing and drying, avoiding defects such as pinholes and bubbles in the grid lines. If the proportion of ethyl cellulose is too high, the paste viscosity will be too high, making it difficult to detach from the screen during printing and easily causing defects such as screen clogging and incomplete printing. If the proportion of ethyl cellulose is too low, the paste viscosity will be too low, and the grid lines will easily sagging and deform after printing, increasing the line width. At the same time, insufficient adhesion will reduce the bonding force between the grid lines and the silicon wafer, making it easy for the grid lines to fall off.
[0042] In some embodiments, the degree of polymerization of the ethyl cellulose is 500 to 1000.
[0043] In some embodiments, the preparation of the organic carrier includes: dissolving ethyl cellulose in terpineol (stirring at 60°C to 80°C for 1 to 3 hours) and adding hydrogenated castor oil as a rheology modifier.
[0044] In some embodiments, the method for preparing the solar cell includes the following steps, such as... Figure 1 As shown: S1. Adding additives, glass powder, and conductive phase to an organic carrier and mixing them together to obtain a conductive material, wherein the additives include rare earth compounds and inert metals; S2. The conductive material is coated on the surface of the solar cell body and cured to form grid lines, thereby obtaining the solar cell.
[0045] In some embodiments of the solar cell fabrication method, before adding the additive, glass powder, and conductive phase to the organic carrier, the additive is ball-milled to a D50 of 50 nm to 100 nm. Pre-milling the additive to this particle size range allows for thorough mixing of specific rare earth compounds, inert metals, and other components, breaking up particle agglomerates in the raw materials. This ensures that each component is uniformly dispersed in the organic carrier during subsequent mixing with the conductive phase and glass powder, avoiding passivation layer defects or battery performance fluctuations caused by uneven local component concentrations. Simultaneously, pre-milling further refines the additive particles, increasing their specific surface area and reactivity, making them more readily react with the glass phase and silver particles during sintering, forming a uniform and continuous passivation layer at the interface, improving anti-PID effect and interfacial contact performance. If the additive particle size is too large, it will lead to uneven component dispersion, preventing the formation of an effective passivation layer in certain areas and increasing the contact resistance of the grid lines. If the particle size is too small, ball milling energy consumption is too high, and the refined particles are prone to re-agglomeration, which is detrimental to uniform dispersion in the slurry.
[0046] In some embodiments of the method for preparing solar cells, during the mixing process in step S1, the mixture is first mixed at low speed (100 rpm, 30 min) using a planetary mixer, and then rolled by a three-roll mill (5 μm gap, 3 times) until the fineness is ≤5 μm.
[0047] In this article, "fineness" refers to the maximum agglomeration particle size of solid particles (including silver powder, glass powder, additives, etc.) in the conductive paste, i.e., the paste fineness value obtained by testing with a scraper fineness gauge. "Gap 5μm" refers to the minimum distance between adjacent rolls of a three-roll mill, used to control the upper limit of grinding solid particles in the paste.
[0048] Grinding the conductive material to a fineness of ≤5μm can effectively break up solid particle agglomerates in the slurry, ensuring that each component is uniformly dispersed in the slurry. This avoids printing defects such as screen clogging, grid line scratches, and grid breakage during printing. At the same time, it can ensure that a continuous and dense conductive network and passivation layer are formed inside the grid line after sintering, reducing the bulk resistance and contact resistance of the grid line and improving the mechanical strength and long-term reliability of the grid line. If the fineness of the slurry is too large, the large particle agglomerates present will not only affect the printing yield, but also lead to increased porosity inside the grid line, decreased conductivity, and discontinuous passivation layer, resulting in poor anti-PID effect.
[0049] Secondly, this application provides a stacked battery, comprising: A crystalline silicon bottom cell, wherein the crystalline silicon bottom cell is the solar cell described above; A perovskite solar cell, wherein the perovskite solar cell is located on one side of the crystalline silicon substrate solar cell.
[0050] Thirdly, this application provides a photovoltaic module, such as Figure 2 As shown, it includes a battery string 100, which includes a plurality of solar cells 101 as described above arranged along a first direction X, and the plurality of battery strings 100 are also arranged along a second direction Y. Solder strip 4, which extends along the first direction X and is arranged along the second direction Y, is used to connect two adjacent solar cells 101 or two stacked cells along the first direction X. Back plate 120, the back plate 120 is located on the side of the solder strip 4 away from the back of the battery string 100.
[0051] In some embodiments, the backsheet is made of polyvinyl fluoride composite film or thermoplastic elastomer, which further isolates water vapor and oxygen, provides good electrical insulation, and provides weather resistance and corrosion resistance, enabling it to withstand harsh environments and long-term exposure to ultraviolet radiation.
[0052] In some embodiments, the backplate is made of glass, which has stronger weather resistance, a longer service life (up to 30 years or more) and better anti-PID performance.
[0053] In some implementations, the solar cells in the cell string can be either monocrystalline silicon cells (high efficiency, deep black color, typically single-cell or half-cell) or polycrystalline silicon cells (slightly lower efficiency, bright blue color, with ice-flower-like patterns), such as half-cell monocrystalline PERC cells. Multiple solar cells are connected in series via solder ribbons (tinned copper ribbons) to achieve the desired voltage.
[0054] In some implementations, photovoltaic modules also include external auxiliary structures such as frames and junction boxes. These external auxiliary structures ensure the safety and lifespan of the module during installation and use. The frame, often made of anodized aluminum alloy, protects the edges of the laminated cover and backsheet, preventing damage during installation and transportation, and providing additional mechanical strength to the entire photovoltaic module. The junction box, typically installed on the back of the backsheet, is the "power outlet" of the photovoltaic module, containing conductive electrodes to collect the direct current generated by the cell strings. In some embodiments, the junction box also contains bypass diodes. When some cell strings are shaded, these cells become power-consuming units (resistors), generating hot spots. The bypass diodes guide current around the shaded cell strings, protecting them from burnout and reducing system power generation losses.
[0055] The present application will now be described in detail through specific embodiments.
[0056] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following embodiments are commercially available.
[0057] Ethyl cellulose: Purchased from Dow Chemical (China) Co., Ltd., degree of polymerization 800.
[0058] Preparation Example 1 Preparation of glass powder: PbO, SiO2 and B2O3 were mixed in a mass ratio of 60:30:10, melted at 1000℃ for 2 hours and then quenched. The mixture was then ball-milled to a D50 of 2μm and a softening temperature of 450℃.
[0059] Preparation Example 2 The preparation method was carried out in accordance with Example 1, except that all B2O3 was replaced with SiO2.
[0060] Preparation Example 3 The preparation method was carried out in accordance with Example 1, except that all PbO was replaced with SiO2.
[0061] Preparation Example 4 The preparation method was carried out in accordance with Example 1, except that all B2O3 was replaced with Bi2O3.
[0062] Preparation Example 5 Preparation of organic carrier: Ethyl cellulose was dissolved in terpineol (stirred at 70°C for 2 hours), and hydrogenated castor oil was added as a rheology modifier. The mass ratio of ethyl cellulose, terpineol, and hydrogenated castor oil was 1:9:0.2.
[0063] Example 1 This embodiment provides a solar cell and its fabrication method, including the following steps: S1. First, mix yttrium oxide, cerium oxide, titanium powder, platinum powder and lanthanum fluoride, and ball mill at 300 rpm for 2 hours to obtain a uniform powder with a D50 of 80 nm. The uniform powder, conductive phase and glass powder are added to an organic carrier, first mixed by planetary stirring (100 rpm) for 30 min, and then rolled three times by a three-roll mill (minimum gap of 5 μm) to a fineness of 3 μm to obtain a conductive material. S2. The conductive material is coated on the front side of an N-type TOPCon cell (182mm×182mm, solar cell body), and cured at 800°C for 1 minute to form a fine grid, thus obtaining the solar cell.
[0064] The conductive material, based on a total mass of 100%, comprises 90% conductive phase (60% spherical silver powder (average particle size of 1.5 μm) and 30% flake silver powder (average length of 2.5 μm)), 4% glass powder obtained in Preparation Example 1, 5.5% organic carrier obtained in Preparation Example 5, and 0.5% additives (0.3% yttrium oxide, 0.1% cerium oxide, 0.05% titanium powder (average particle size of 30 nm), 0.02% platinum powder (average particle size of 20 nm), and 0.03% lanthanum fluoride).
[0065] Example 2 The method was implemented in accordance with Example 1, except that the average particle size of the titanium powder was 20 nm and the average particle size of the platinum powder was 10 nm.
[0066] Example 3 The method was implemented in accordance with Example 1, except that the average particle size of the titanium powder was 50 nm and the average particle size of the platinum powder was 30 nm.
[0067] Example 4 The procedure was carried out as in Example 1, except that all cerium oxide was replaced with lanthanum fluoride.
[0068] Example 5 The procedure was carried out as described in Example 1, except that all titanium powder was replaced with platinum powder.
[0069] Example 6 The method was implemented in accordance with Example 1, except that the yttrium oxide content in the additive was 0.2% and the cerium oxide content was 0.2%.
[0070] Example 7 The method was implemented in accordance with Example 1, except that the yttrium oxide content in the additive was 0.1% and the cerium oxide content was 0.3%.
[0071] Example 8 The method was implemented in accordance with Example 1, except that the average particle size of the spherical silver powder was 0.5 μm and the average length of the flake silver powder was 1 μm.
[0072] Example 9 The method was implemented in accordance with Example 1, except that the average particle size of the spherical silver powder was 3 μm and the average length of the flake silver powder was 5 μm.
[0073] Example 10 The method was implemented in accordance with Example 1, except that the content of spherical silver powder was 30% and the content of flake silver powder was 60%.
[0074] Example 11 The procedure was carried out in accordance with Example 1, except that all the glass powder obtained in Preparation Example 1 was replaced with the glass powder obtained in Preparation Example 2.
[0075] Example 12 The procedure was carried out in accordance with Example 1, except that all the glass powder obtained in Preparation Example 1 was replaced with the glass powder obtained in Preparation Example 3.
[0076] Example 13 The procedure was carried out in accordance with Example 1, except that all the glass powder obtained in Preparation Example 1 was replaced with the glass powder obtained in Preparation Example 4.
[0077] Examples 14 and 15 The procedure was carried out as described in Example 1, except that the content of each component in the conductive material was different, as shown in Table 1. Table 1
[0078] Comparative Example 1 The procedure was carried out as in Example 1, except that lanthanum fluoride was completely replaced with cerium oxide.
[0079] Comparative Example 2 The procedure was carried out as described in Example 1, except that all platinum powder was replaced with titanium powder.
[0080] Comparative Example 3 The procedure was carried out as described in Example 1, except that all yttrium oxide was replaced with cerium oxide.
[0081] Solar cells prepared using the solar cells obtained in Examples 1-15 and the solar cells prepared in Comparative Examples 1-3 were respectively used to prepare solar cells. Figure 2 The photovoltaic modules shown are illustrated, and PID (potential-induced degradation) tests were performed on each module. The test results are shown in Table 2. Table 2
[0082] As shown in Table 2, comparing Example 1 (additive containing 0.3% yttrium oxide + 0.1% cerium oxide + 0.03% lanthanum fluoride, efficiency decay rate 0.78%) with Comparative Example 1 (replacing all lanthanum fluoride with cerium oxide, i.e., a compound without lanthanum, efficiency decay rate 4.30%), it is evident that introducing lanthanum compounds (lanthanum fluoride) into the rare earth system is crucial for improving PID resistance. Comparative Example 1 and Comparative Example 3 (replacing all yttrium oxide with cerium oxide, i.e., a compound without heavy rare earth compounds, efficiency decay rate 4.69%) further verify the key role of heavy rare earth compounds (yttrium oxide) in the rare earth synergistic system. Comparative Examples 1 and 3 both contain only light rare earth compounds (cerium oxide), lacking either lanthanum or heavy rare earth compounds, resulting in a significantly increased PID decay rate. This indicates that a single rare earth compound cannot achieve effective ion capture and complexation protection; the rare earth synergistic system is the core of the anti-PID technology solution in this application.
[0083] Comparing Example 1 (containing 0.02% platinum powder + 0.05% titanium powder, with an efficiency decay rate of 0.78%) with Comparative Example 2 (where all platinum powder was replaced with titanium powder, i.e., no inert metal was present, with an efficiency decay rate of 5.08%), it is evident that the inert metal platinum plays an irreplaceable role in anti-PID systems. As a highly chemically inert noble metal, platinum forms a stable passivation and protective structure at the gate interface, effectively blocking inion migration and electrochemical corrosion paths; while titanium powder alone cannot achieve the same interface passivation effect.
[0084] Comparing Example 1 and Example 5 (where all titanium powder was replaced with platinum powder, resulting in an efficiency decrease of 2.34%), it is evident that titanium powder is equally indispensable in the additives. Although platinum powder replacing titanium powder still yielded better results than the comparative example, the decrease rate was significantly higher than in Example 1, indicating that the synergistic effect of titanium and platinum can achieve optimal passivation.
[0085] Comparing Example 1 (using PbO:SiO2:B2O3 = 60:30:10 glass powder from Preparation Example 1, efficiency degradation rate 0.78%), Example 11 (using boron-free glass powder from Preparation Example 2, efficiency degradation rate 1.95%), Example 12 (using lead-free glass powder from Preparation Example 3, efficiency degradation rate 2.76%), and Example 13 (using glass powder from Preparation Example 4 with Bi2O3 replacing B2O3, efficiency degradation rate 1.56%), it can be seen that the lead- and boron-containing silicate glass powder system has the best overall performance. Although the degradation rate of Example 13 after replacing B2O3 with Bi2O3 was 1.56%, which is better than Examples 11 and 12, it is still worse than Example 1, indicating that B2O3 plays a better role than Bi2O3 in the glass powder system of this application.
[0086] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.
Claims
1. A solar cell, characterized in that, include: Solar cell body; A grid line, wherein the grid line is formed by curing a conductive material, the conductive material including additives, the additives comprising rare earth compounds and inert metals; Wherein, the rare earth compound is a mixture of lanthanum compounds and heavy rare earth compounds, or, The rare earth compounds are non-lanthanum light rare earth compounds, lanthanum compounds, and mixtures of heavy rare earth compounds.
2. The solar cell according to claim 1, characterized in that, The inert metal is selected from at least one of platinum, palladium, gold and silver, and the additive also includes titanium-containing materials.
3. The solar cell according to claim 2, characterized in that, The inert metal includes platinum powder, the titanium-containing material includes titanium powder, the titanium powder has an average particle size of 20nm~50nm, and the platinum powder has an average particle size of 10nm~30nm.
4. The solar cell according to claim 1 or 3, characterized in that, The lanthanum compound is lanthanum oxide and / or a lanthanum halide, the non-lanthanum light rare earth compound is selected from at least one of cerium compounds, praseodymium compounds and neodymium compounds, and the heavy rare earth compound is selected from at least one of yttrium compounds, gadolinium compounds and scandium compounds.
5. The solar cell according to claim 3, characterized in that, The rare earth compound is a mixture of non-lanthanum light rare earth compounds, lanthanum compounds, and heavy rare earth compounds, wherein the non-lanthanum light rare earth compound is cerium oxide, the heavy rare earth compound is yttrium oxide, the lanthanum compound is lanthanum fluoride, and the mass ratio of cerium oxide to yttrium oxide is 1:(2~4).
6. The solar cell according to claim 2, characterized in that, Based on the total mass of the conductive material being 100%, the content of the additive is 0.175% to 1.05%.
7. The solar cell according to claim 6, characterized in that, The additives include lanthanum fluoride, cerium oxide, yttrium oxide, titanium powder, and platinum powder, wherein the content of yttrium oxide is 0.1% to 0.5%, the content of cerium oxide is 0.05% to 0.3%, the content of titanium powder is 0.01% to 0.1%, the content of platinum powder is 0.005% to 0.05%, and the content of lanthanum fluoride is 0.01% to 0.1%.
8. The solar cell according to claim 1 or 7, characterized in that, The conductive material further includes a conductive phase, glass powder, and an organic carrier. Based on the total mass of the conductive material (100%), the content of the conductive phase is 85% to 92%, the content of the glass powder is 2% to 5%, and the content of the organic carrier is 4% to 8%.
9. The solar cell according to claim 8, characterized in that, The conductive phase includes spherical silver powder and flake silver powder, wherein the average particle size of the spherical silver powder is 0.5 μm to 3 μm, and the average length of the flake silver powder is 1 μm to 5 μm.
10. The solar cell according to claim 9, characterized in that, The mass ratio of the spherical silver powder to the flake silver powder is (1~3):
1.
11. The solar cell according to claim 8, characterized in that, The glass powder includes lead and boron silicate glass powder, wherein the raw materials of the silicate glass powder include lead oxide, silicon oxide and boron oxide, and the mass ratio of lead oxide, silicon oxide and boron oxide is (5~7):(2~4):
1.
12. The solar cell according to claim 8, characterized in that, The organic carrier comprises ethyl cellulose and terpineol, wherein the mass ratio of ethyl cellulose to terpineol is 1:(8~10).
13. The solar cell according to claim 12, characterized in that, The degree of polymerization of the ethyl cellulose is 500~1000.
14. A stacked battery, characterized in that, include: A crystalline silicon bottom cell, wherein the crystalline silicon bottom cell is a solar cell according to any one of claims 1 to 13; A perovskite solar cell, wherein the perovskite solar cell is located on one side of the crystalline silicon substrate solar cell.
15. A photovoltaic module, characterized in that, The battery string includes a plurality of solar cells according to any one of claims 1 to 13 arranged along a first direction, or a stacked battery according to claim 14, and the plurality of battery strings are further arranged along a second direction; A solder strip extending along a first direction and arranged along a second direction, the solder strip being used to connect two adjacent solar cells or two stacked cells along the first direction; A backplate, located on the side of the solder strip away from the back of the battery string.